Perbandingan Struktur Modal Perusahaan Property dan Konstruksi Bangunan Periode 2015-2019 - Yusniawati, Nialena; Chomsatu, Yuli; Suhendro, Suhendro (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
ABSTRACTCapital structure is a comparison of own capital with foreign capital owned by each company. Capital alone can be divided into retained earnings and company ownership. Meanwhile, foreign capital is short-term debt or long-term debt. The good and bad conditions of the company can be determined through the capital structure. Through the capital structure, the company can allocate funds owned for appropriate business activities as well as useful for the continuity of the company. In general, factors that affect the company's capital structure include profitability, liquidity, company size, sales growth, and asset structure.This study aims to find out the different influences of capital structures on property companies and building construction. This research uses property and building construction companies listed on the Indonesia Stock Exchange in 2015-2019.The result of this study profitability affects the capital structure of property companies, while in building construction companies profitability has no effect on the capital structure. Liquidity in property companies affects the capital structure. This is the same as the result of building construction companies where liquidity affects the capital structure. In property companies the size of the company has an influence on the capital structure, as well as building construction companies that the variable size of the company affects the capital structure. Sales growth has an influence on the capital structure in property companies, while building construction companies sales growth has no effect on the capital structure. The structure of the property company's assets affects the capital structure. The same indicates that the asset structure of building construction companies affects the capital structure. The difference in the influence of the capital structure of property companies is influenced by profitability, liquidity, company size, sales growth, and asset structure. For the capital structure of building construction is influenced by liquidity, company size, and asset structure. As for variable profitability and sales growth in building construction companies has no effect on the capital structure. Keywords: Profitability, Liquidity, Company Size, Sales growth, Asset Structure, Capital Structure